2011
DOI: 10.1590/s1677-55382011000100009
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve for radical retropubic prostatectomy

Abstract: Purpose:The learning curve is a period in which the surgical procedure is performed with difficulty and slowness, leading to a higher risk of complications and reduced effectiveness due the surgeon's inexperience. We sought to analyze the residents' learning curve for open radical prostatectomy (RP) in a training program. Materials and Methods:We conducted a prospective study from June 2006 to January 2008 in the academic environment of the University of São Paulo. Five residents operated on 184 patients durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
1
8
0
4
Order By: Relevance
“…Three studies investigated the learning curve for both open and LRP, while one study evaluated the learning curve for perineal prostatectomy (Table ). Vickers et al.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies investigated the learning curve for both open and LRP, while one study evaluated the learning curve for perineal prostatectomy (Table ). Vickers et al.…”
Section: Resultsmentioning
confidence: 99%
“…[9] In this sense, several factors may play an important role in the learning curve, including those related to the surgeon, such as confidence and experience with other surgical procedures, as well as those related to the team members involved in the procedures. The number of cases performed by the surgeon and the volume of surgeries in a given center may undoubtedly delineate the course of surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the number of cases required to develop proficiency in this procedure is of the order of 250–1000 . During this learning curve, positive surgical margins (PSMs) and resultant oncological outcomes have been shown to be inferior …”
Section: Introductionmentioning
confidence: 99%